2021
DOI: 10.3390/ijms222111305
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Oxidation and Anti-Inflammatory Potency Evaluation of Ferulic Acid Derivatives Obtained through Virtual Screening

Abstract: Various factors such as ultraviolet rays can cause a continuous threat to our skin, resulting in inflammation or oxidation problems. Ferulic acid (FA), with certain antioxidant and anti-inflammatory properties, is widely used in many cosmetics, even used to treat various diseases in the clinic. In this study, the FA structural skeleton was used to search for FA derivatives. Then, molecular docking, the rule of five, and Veber rules were performed to virtually screen compounds that can bind to proteins with a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…This finding could be attributed to the high abundance and diversity of phenolic compounds in the BP fraction ( Table 3 ). Ferulic acid and its derivatives, a major phenolic compound in BP extracts of WB, prevented inflammation and oxidative stress in LPS-stimulated RAW264.7 cells by suppression of intracellular ROS and inflammatory mediators, including iNOS, COX-2, TNF-alpha and IL-6 [ 78 ]. Besides, in a recent in vivo study of El-gogary et al [ 79 ], the administration of FA in lipid nanocapsules reduced significantly the TNF-α and NF-kB levels in colorectal cancer-induced rats.…”
Section: Resultsmentioning
confidence: 99%
“…This finding could be attributed to the high abundance and diversity of phenolic compounds in the BP fraction ( Table 3 ). Ferulic acid and its derivatives, a major phenolic compound in BP extracts of WB, prevented inflammation and oxidative stress in LPS-stimulated RAW264.7 cells by suppression of intracellular ROS and inflammatory mediators, including iNOS, COX-2, TNF-alpha and IL-6 [ 78 ]. Besides, in a recent in vivo study of El-gogary et al [ 79 ], the administration of FA in lipid nanocapsules reduced significantly the TNF-α and NF-kB levels in colorectal cancer-induced rats.…”
Section: Resultsmentioning
confidence: 99%
“…Neuroinflammation is a driver for traumatic exacerbation via cascade inflammatory infiltration and cellular lesion (Delage et al, 2021 ). Increasing reports have proven that the antioxidation and antiinflammatory properties of ferulic acid is well recognized in preclinical studies (Shi et al, 2021 ). Current findings demonstrated that an antineuroinflammation action may be one of the pharmacological mechanisms of ferulic acid in treating TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic acids have many health benefits. These include anti-inflammatory and antioxidative actions ( 81 , 82 ), antidiabetic ( 83 ), and hepatoprotective ( 84 ), and antineoplastic ( 85 , 86 ). Caffeic acid (3,4-dihydroxycinnamic acid) phenethyl ester (CAPE) is reported cytotoxic and anti-proliferative actions on RPMI 8226, H929, U266 and ARH77 cell lines, and also synergises with bortezomib in growth inhibition and reduction of NF-kB binding activity and IL6 levels ( 87 ).…”
Section: Flavonoidsmentioning
confidence: 99%